Rapid synthesis, kinetics and thermodynamics of binary Mn 0.5Ca0.5(H2PO4)2 • H2O - Boonchom, Banjong; Danvirutai, Chanaiporn (My University, 2009)
The binary manganese and calcium dihydrogen phosphate monohydrate Mn 0.5Ca0.5(H2PO4)2 • H2O was synthesized by a rapid and simple co-precipitation method using phosphoric acid, manganese metal, and calcium carbonate at ambient temperature. Thermal transformation shows complex processes and the final decomposed product was the binary manganese calcium cyclotetraphosphate MnCaP4O12. The activation energies of some decomposed steps were calculated by Kissinger method. Activated complex theory has been applied to each step of the reactions and the thermodynamic functions are calculated. These values for transformation stages showed that they are non-spontaneous processes without the introduction of heat. The differences of physical and chemical properties of the synthesized compound and its decomposed product are compared with M(H2PO4)2 • H2O and M2P4O12 (M = Mn and Ca), which indicate the effects of the presence of Ca ions in substitution of Mn ions and confirm the formation of solid solution. © 2009 Akadémiai Kiadó, Budapest, Hungary.
Keywords: A rapid co-precipitation; Kinetics; Manganese and calcium dihydrogen phosphate; Thermodynamics